1999
DOI: 10.1016/s0006-3495(99)76946-8
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Analysis of Chain-Melting Transition Temperatures for Monounsaturated Phospholipid Membranes: Dependence on cis-Monoenoic Double Bond Position

Abstract: Unsaturated phospholipid is the membrane component that is essential to the dynamic environment needed for biomembrane function. The dependence of the chain-melting transition temperature, T(t), of phospholipid bilayer membranes on the position, n(u), of the cis double bond in the glycerophospholipid sn-2 chain can be described by an expression of the form T(t) = T(t)(c)(1 + h'(c)|n(u) - n(c)|)/(1 + s'(c)|n(u) - n(c)|), where n(c) is the chain position of the double bond corresponding to the minimum transition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
28
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 14 publications
6
28
0
Order By: Relevance
“…When the double-bond position is moved from the middle of the chain toward the lipid head group, the average area per PC is reduced as well, but now the reduction is substantially smaller, ;0.007 nm 2 , close to the margin of error (60.003 nm 2 ). Nonetheless, it is clear that A PC has a maximum when the double bond resides in the middle of an acyl chain, in line with experiments (18) indicating that the main transition temperature is smallest when the double bond is located in the middle of the chain. Comparison with experimental values shows good agreement: Petrache et al (42) obtained an average area per lipid of 0.66 nm 2 at 338 K for a DSPC bilayer (0.670 nm 2 in our simulations), and x-ray data for a fully hydrated DOPC bilayer provides a range of 0.721-0.725 nm 2 for the area per lipid (43-46) (0.731 nm 2 6 0.003 nm 2 in our simulations).…”
Section: Area Per Molecule and Condensing Effectsupporting
confidence: 86%
See 1 more Smart Citation
“…When the double-bond position is moved from the middle of the chain toward the lipid head group, the average area per PC is reduced as well, but now the reduction is substantially smaller, ;0.007 nm 2 , close to the margin of error (60.003 nm 2 ). Nonetheless, it is clear that A PC has a maximum when the double bond resides in the middle of an acyl chain, in line with experiments (18) indicating that the main transition temperature is smallest when the double bond is located in the middle of the chain. Comparison with experimental values shows good agreement: Petrache et al (42) obtained an average area per lipid of 0.66 nm 2 at 338 K for a DSPC bilayer (0.670 nm 2 in our simulations), and x-ray data for a fully hydrated DOPC bilayer provides a range of 0.721-0.725 nm 2 for the area per lipid (43-46) (0.731 nm 2 6 0.003 nm 2 in our simulations).…”
Section: Area Per Molecule and Condensing Effectsupporting
confidence: 86%
“…Those studies showed that ordering within a membrane was weakest when the double bond was located in the middle of an acyl chain. For comparison, other experiments have shown (18) that the main transition temperature of single-component lipid bilayers with monounsaturated acyl chains has a minimum when the double bond resides in the middle of the hydrocarbon chain, indicating that membrane order is minimized under those conditions. Both simulations and experiments therefore support the view that by favoring monounsaturated acyl chains with a double bond in the middle of a chain, nature promotes membrane fluidity.…”
Section: Introductionmentioning
confidence: 96%
“…Unfortunately, time did not allow measurement of γ vs. pH curves for compound 9 (oleyl analogue). However, it has been observed [49,50] that amphiphiles with unsaturated alkyl tails have analogous aggregation behaviour to saturated compounds containing 2–4 fewer methylene units. We therefore expect the pH c of compound 9 to lie within the endosomal range.…”
Section: Resultsmentioning
confidence: 99%
“…The position of the cis unsaturation and branching in the chain has an effect on the T m value as does the individual headgroup i.e. phosphatidylethanolamine (PE) or phosphatidylcholine (PC) (Cevc, 1991;Marsh, 2013Marsh, , 1999, however the introduction of a single unsaturation into a saturated chain causes one of the biggest changes to T m and membrane order. Thus the ratio sats/unsats accounts for the major structural contribution of each individual compositional lipid species to the mixed membrane order parameter.…”
Section: Introductionmentioning
confidence: 99%